GeoFarmer App: A tool to complement extension services and foster active farmers participation and knowledge exchange - Eitzinger, Anton; Bartling, Mona; Feil, Christian; Bonilla Findji, Osana; Andrieu, Nadine; Jarvis, Andy (International Center for Tropical Agriculture, 2020)
GeoFarmer is an app designed to support experience exchanges between farmers – be they positive or negative – so that they can learn from each other by asking questions and by sharing suggestions on how their crop, animal and farm management can be improved. Project implementers can also use it to obtain continuous feedback and follow up with farmers during project implementation. GeoFarmer is a flexible tool that can be used for data collection (including spatial functionalities and location data to geo-reference information), as a knowledge library, or for efficient monitoring and evaluation of agricultural technologies and practices implemented by farmers.